The investigation of relationship between behavioral and decisional procrastination with personality characteristics among students of Tehran Universities - Tamannaeifar, Shima; Gharaee, Banafsheh; Bakhshizade, Ali; Sheybani, Farshad (International Journal of Applied Behavioral Sciences, 2016)
Introduction: The present study was carried out with the aim to investigate the relationship between behavioral and decisional procrastination with personality characteristic among students of Tehran Universities. Methods: the number of samples in this research includes 400 students (114 female and 286 male) from Tehran universities that selected using random cluster-multistage sampling and completed behavioral, decisional procrastination and five factor personality questionnaire. Data were analyzed using descriptive statistics, independent t-test and Pearson correlation. Results: Data indicated that the most prevalence of behavioral and decisional procrastination was between Shahid Beheshti and Tabatabaie universities respectively. On the other hand, procrastination was related positively to neuroticism and negatively to consciousness, extraversion and agreeableness. Also, there were no relationship between procrastination and openness. Conclusion: Considering the positive relationship between procrastination and neuroticism and negative relationship with consciousness, extroversion and agreeableness, attention to personality characteristics can reduce procrastination and in turn, improve engagement in educational activities. Declaration of Interest: None.